Online mode as a motivation for library initiatives (on the example of the Russian State Library of Arts) - Inna A. Vaganova (Библиосфера)
The article generalizes and systematizes exhibition, educational and project activities of The Russian State Library of Arts (RSLA) in terms of measures related to self-isolation under the threat of coronavirus infection (COVID-19) spreading. The necessary and sufficient conditions for effective work in remote mode are considered. Emphasis is made on the organization of work on projects. The conclusion is made on the strategic importance of teamwork, network interaction of employees, and operational coordination of work. It is noted that the library managed to significantly expand its Internet resources. This was reflected in the development and presentation of virtual exhibitions, thematic online lectures and publications, video reviews, virtual excursions, meetings on the Zoom platform, in the reorganization and adaptation of planned events to new conditions.The important organizational steps were: mastering the necessary software products, including video editing, and psychological and pedagogical skills to retain the audience; understanding the need to discuss virtual expositions in working groups and exhibition councils.All this made it possible not only to preserve the old audience, but also to attract a new one for RSLA.A conclusion is also made for the future: when planning events and publications in the web space, it is very important to balance the issues of lectures, reviews, video meetings, modern and retrospective topics, archival recordings and new publications.